Hutchison's atlas of paediatric physical diagnosis - Goel, Krishna M.; Carachi, Robert (Jaypee Brothers Medical Publishers (P) LTD, 2014)
Guide to diagnosis of paediatric diseases and disorders with emphasis on accurate history taking and thorough physical examination. Highly experienced, UK editors and more than 1600 images and illustrations included.